2013
DOI: 10.1371/journal.pone.0060332
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Dietary Salt Intake Induces Coordinated Dynamics of Monocyte Subsets and Monocyte-Platelet Aggregates in Humans: Implications in End Organ Inflammation

Abstract: BackgroundMonocyte activation and tissue infiltration are quantitatively associated with high-salt intake induced target organ inflammation. We hypothesized that high-salt challenge would induce the expansion of CD14++CD16+ monocytes, one of the three monocyte subsets with a pro-inflammatory phenotype, that is associated with target organ inflammation in humans.Methodology/Principal FindingsA dietary intervention study was performed in 20 healthy volunteers, starting with a 3-day usual diet and followed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 51 publications
4
54
0
1
Order By: Relevance
“…dietary salt intake can induce inflammation. 16 Recently, Telini et al have reported that dietary sodium restriction is associated with the attenuation of the inflammatory process, without changes in blood pressure and ECW, suggesting inhibition of a salt-induced inflammatory process. 17 Similarly, the same group has observed that dialysate sodium reduction give rise to similar results.…”
Section: Discussionmentioning
confidence: 99%
“…dietary salt intake can induce inflammation. 16 Recently, Telini et al have reported that dietary sodium restriction is associated with the attenuation of the inflammatory process, without changes in blood pressure and ECW, suggesting inhibition of a salt-induced inflammatory process. 17 Similarly, the same group has observed that dialysate sodium reduction give rise to similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our recent work also demonstrated that a high-salt diet can induce circulating monocyte pro-inflammatory activation and is associated with end-organ inflammation (14). The role of monocyte/macrophage infiltration in initiating AT hypoxia and altered insulin sensitivity has been suggested as a key pathophysiological process during obesity (2).…”
Section: Introductionmentioning
confidence: 90%
“…Flow cytometry analysis of circulating monocyte subsets was performed using a CD14-, CD16-and CD86-based protocol according to our previous work (14). Detailed methods and gating strategies are presented in Supporting Information sFigure 1.…”
Section: Flow Cytometry Analysis Of Monocyte Subsetsmentioning
confidence: 99%
See 2 more Smart Citations